The shape of fantasy : investigating the structure of American heroic epic fantasy - Palmer-Patel, C. (Routledge research in American literature and culture., 2020)
The Shape of Fantasy is an in-depth look at Heroic Epic Fantasy. It depicts structural and narrative patterns with models stemming from science and philosophy. Although Fantasy Fiction is generally defined by its impossibility, Fantasy Fiction not an illogical form. It is, in fact, governed by a sense of rules and structure, one that reflects our current understanding of space-time and cosmology. These models are an integral part of the structure of Heroic Epic Fantasy itself. Thus, this book introduces new ways of perceiving current productions of the Fantasy genre. In doing so, it also explores how Fantasy Fiction exhibits a conscious awareness of its own form.